Effect of a perinatal care quality improvement package on patient satisfaction: a secondary outcome analysis of a cluster-randomised controlled trial - Ashish KC; Anna Bergstrom; Mats Målqvist; Dipak Chaulagain; Olivia Brunell (BMJ Open)
Objective To investigate the effect of a quality improvement (QI) package on patient satisfaction of perinatal care.Design Secondary analysis of a stepped-wedge cluster-randomised controlled trial. Participating hospitals were randomised by size into four different wedges.Setting 12 secondary-level public hospitals in Nepal.Participants Women who gave birth in the hospitals at a gestational age of ≥22 weeks, with fetal heart sound at admission. Adverse outcomes were excluded. One hospital was excluded due to data incompleteness and four low-volume hospitals due to large heterogeneity. The final analysis included 54 919 women.Intervention Hospital management was engaged and facilitators were recruited from within hospitals. Available perinatal care was assessed in each hospital, followed by a bottle-neck analysis workshop. A 3-day training in essential newborn care was carried out for health workers involved in perinatal care, and a set of QI tools were introduced to be used in everyday practice (skill-checks, self-assessment checklists, scoreboards and weekly Plan–Do–Study–Act meetings). Refresher training after 6 months.Outcome measure Women’s satisfaction with care during childbirth (a prespecified secondary outcome).Results The likelihood of women being overall satisfied with care during childbirth increased after the intervention (adjusted OR (aOR): 1.66, 95% CI: 1.59 to 1.73). However, the proportions of overall satisfaction were low (control 58%, intervention 62%). Women were more likely to be satisfied with education and information from health workers after intervention (aOR: 1.34, 95% CI: 1.29 to 1.40) and to have been treated with dignity and respect (aOR: 1.81, 95% CI: 1.52 to 2.16). The likelihood of having experienced abuse during the hospital stay decreased (aOR: 0.42, 95% CI: 0.34 to 0.51) and of being satisfied with the level of privacy increased (aOR: 1.14, 95% CI: 1.09 to 1.18).Conclusions Improvements in patient satisfaction were indicated after the introduction of a QI-package on perinatal care. We recommend further studies on which aspects of care are most important to improve women’s satisfaction of perinatal care in hospitals in Nepal.Trial registration number ISRCTN30829654.